2004
DOI: 10.1258/1357633041424430
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a teleradiology and videoconferencing system

Abstract: We developed a teleradiology system linking a general hospital on Sado Island to tertiary care hospitals in Niigata City. The island is 40 km from Niigata City on the mainland and has only one diagnostic radiologist (for 72,000 islanders). Fibre optic cables between Sado Island and Niigata City were used for transmission. The introduction of the teleradiology system facilitated diagnostic and therapeutic consultation with specialists in Niigata City. The performance of the system was evaluated (on a scale of 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…The barriers to the implementation of telehealth were: 19,33,44,45,48,53,54,57,67 Software incompatibility between two or more countries or institutions; Internet congestion causing delays or a low frame-rate of the video pictures and interruptions and delays in voice transmission; High communication charges and equipment costs; Other communication problems like a change of IP address and configuration of the receiving network, a broken cable at the host network and alteration of the cabling at the host site without authorization; Untrained service providers including physicians and staff; Small sample size and lack of follow up; Poor infrastructure and other logistical challenges. …”
Section: Resultsmentioning
confidence: 99%
“…The barriers to the implementation of telehealth were: 19,33,44,45,48,53,54,57,67 Software incompatibility between two or more countries or institutions; Internet congestion causing delays or a low frame-rate of the video pictures and interruptions and delays in voice transmission; High communication charges and equipment costs; Other communication problems like a change of IP address and configuration of the receiving network, a broken cable at the host network and alteration of the cabling at the host site without authorization; Untrained service providers including physicians and staff; Small sample size and lack of follow up; Poor infrastructure and other logistical challenges. …”
Section: Resultsmentioning
confidence: 99%
“…As network and computing capabilities improve, telemedicine is increasingly moving away from the now relatively trivial transfer of static images [18][19][20] to more complex clinical activities, such as telesurgery 21 or, in our case, dynamic treatment planning.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the study suggested that the implementation of a cursor pointer will enhance the consultation process, especially for congenital heart disease. Moreover, the system has also been implemented in teleradiology consultation [42,43] as shown in Figure 4(A). A similar approach has been adopted in telementoring of gynecological surgery where a cursor pointer is used to highlight the structure and landmark anatomy on the monitor of the operating room [44].…”
Section: Reviewmentioning
confidence: 99%